Diseño y construcción de un sistema de alimentación de materia prima para la elaboración de balanceado - Albán Bautista, Lisandro David (2022)
This technological project consists of the design and implementation of a system that allows the supply of raw material in the process of manufacturing balanced by using helical shafts, in order to mitigate the effects of moving components manually, since this activity demands excessive physical effort by the operator and high production time in the execution of labor activities in the "AVÍCOLA BAUTISTA" of Salcedo canton. With the installation of the raw material transport system, the operator is replaced in the process of transferring the components of the poultry feed, reducing by sixty percent the labor risk that this activity represents and reducing the period of use of the machinery, since the raw material transfer operation will be carried out by helical conveyors, which use the technology of a worm screw based on the norms specified in the manual published by the company "Martin helicoidales" which is based on the guidelines of the CEMA that establishes the characteristics of the machines according to certain materials, from which the necessary variables are obtained for the design of the supply process, such as the speed of rotation and power of the system that allows dimensioning the structures that conform the conveyors and the selection of adequate elements, obtaining as a result a set of machines that allow reducing in one hour the production time.